2015
DOI: 10.1080/13527266.2015.1005115
|View full text |Cite
|
Sign up to set email alerts
|

Exploring effects of source similarity, message valence, and receiver regulatory focus on yelp review persuasiveness and purchase intentions

Abstract: This study is among the first to investigate the impact of message, source, and receiver characteristics on user attitudes toward Yelp reviews, with the subsequent impact of these attitudinal evaluations on review persuasiveness. Specifically, it examines the roles of review valence (positive/negative) and sidedness (one-sided/two-sided), as well as perceived similarity with the reviewer, on user perceptions of helpfulness, trustworthiness, and credibility of the review. The study also tests moderating effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
66
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 59 publications
6
66
1
3
Order By: Relevance
“…Third, the cognitive processing of text is highly contextual and could be influenced by reviewer characteristics (Pentina, Bailey, & Zhang, 2015). As a result, reviewer characteristics could influence consumers' perceptions about the review (Zhang, Wu, & Mattila, 2014).…”
mentioning
confidence: 99%
“…Third, the cognitive processing of text is highly contextual and could be influenced by reviewer characteristics (Pentina, Bailey, & Zhang, 2015). As a result, reviewer characteristics could influence consumers' perceptions about the review (Zhang, Wu, & Mattila, 2014).…”
mentioning
confidence: 99%
“…engage in positive or negative word of mouth (De Matos and Rossi, 2008;Sweeney et al, 2005;Harrison-Walker, 2001). A limited number of studies till date have shown that the impact of regulatory focus on product decisions can be moderated by the word of mouth valence (Pentina et al, 2015;Zhang et al, 2010), albeit with interesting differences. Zhang et al (2010) finds when regulatory focus is matched with promotion (prevention) consumption goals, positive (negative) word of mouth is more persuasive than negative (positive) word of mouth.…”
mentioning
confidence: 99%
“…For example, they do not study the effect of word of mouth valence on product attitude and choice, a variable that is important for regulatory focus literature (Motyka et al, 2014) (Gap 3). Further, the limited research that connects regulatory focus and word of mouth (Pentina et al, 2015;Zhang et al, 2010) fail to consider the recent theoretical developments in the regulatory focus literature, and just propagate their hypotheses based on match between regulatory foci and valence of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 information. For example, both Pentina et al (2015) and Zhang et al (2010) argue that promotion (prevention) foci are more sensitive to positive (negative) information as it helps them to achieve (avoid) positive versus negative outcomes.…”
mentioning
confidence: 99%
“…is. In this regard, some researchers have tried to use Yelp reviews to analyze ratings of business venues from different perspectives, including influence of consumer reviews on purchase decisions (e.g., [14,20]), fraud and credibility of reviews (e.g., [12,15]), prediction of venue ratings (see [6,7,9,10,16,29]), venue recommendation [4,13,22,30]. Although more and more researchers are interested in Yelp data, exploiting geospatial information of Yelp data is missing in most of the aforementioned studies.…”
Section: Introductionmentioning
confidence: 99%